2018
DOI: 10.1002/lary.27219
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy induces antifibrotic alterations in primary human vocal fold fibroblasts

Abstract: NA Laryngoscope, 128:E323-E331, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
(110 reference statements)
0
22
0
Order By: Relevance
“…The sublethal doses of ALA and 580-740 nm light irradiation on human dermal fibroblasts was shown to in vitro induce matrix metalloproteinase 1 and matrix metalloproteinase 3 expression in a singlet oxygen-dependent way while reducing collagen type I mRNA expression[126]. In vitro treatment of primary human vocal fold fibroblasts with sublethal (200µM) ALA-based PDT was shown to significantly alter the expression of genes related to ECM remodelling[127]. Thus, the expressions of TGF-b1, COL1A2, COL3A1, fibronectin and elastin were reduced, while the expression of MMP1 was increased.…”
mentioning
confidence: 99%
“…The sublethal doses of ALA and 580-740 nm light irradiation on human dermal fibroblasts was shown to in vitro induce matrix metalloproteinase 1 and matrix metalloproteinase 3 expression in a singlet oxygen-dependent way while reducing collagen type I mRNA expression[126]. In vitro treatment of primary human vocal fold fibroblasts with sublethal (200µM) ALA-based PDT was shown to significantly alter the expression of genes related to ECM remodelling[127]. Thus, the expressions of TGF-b1, COL1A2, COL3A1, fibronectin and elastin were reduced, while the expression of MMP1 was increased.…”
mentioning
confidence: 99%
“…VF fibrosis is the result of the formation of scar tissue on VF lamina propria as a result of damage and can lead to voice disorders. Although scarring is generally important for wound healing, abnormal regenerative events such as excessive scar formation and inflammatory responses can lead to tissue fibrosis (Zhang et al, 2018). Due to excessive scarring, VF lamina propria tissue is replaced by fibrotic tissue with a disorganized ECM (Erndt‐Marino et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches to VF fibrosis include scar excision, biomaterial injection or implantation, and localized steroid injection. However, most of these treatments produce inconsistent and unsatisfactory results (Kishimoto et al, 2019; Zhang et al, 2018). Therefore, there is a crucial need to develop a more consistent and effective strategy for VF fibrosis that has minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that PDT leads to minimal amounts of scarring, a crucial factor in voice outcomes. 79 However, there are few studies that encompassed voice outcomes. One study led by von Beckerath et al 80 looked at voice quality post PDT treatment of laryngeal cancer using a subjective pre and post-PDT assessment performed by a phonometrist.…”
Section: Clinical Usesmentioning
confidence: 99%